ANALISIS KEBUTUHAN BAHAN AJAR E-MODUL MEKANIKA BAHAN BERBASIS PROBLEM BASED LEARNING DI UNIVERSITAS NEGERI JAKARTA - Annisa Nurrahmawati (JURNAL PENDIDIKAN DAN KEGURUAN, 2024)
This study aims to analyse students' needs for E-module teaching materials in the Mechanics of Materials course at the Building Engineering Education Study Program, State University of Jakarta. This research uses a descriptive survey method with a data collection method in the form of a questionnaire with a simple random sampling technique consisting of 40 respondents of undergraduate students of the Building Engineering Education Department Class of 2020-2022. The questionnaire filling period was 15 - 18 May 2024. The results of the needs analysis show that 95% choose E-modules and 80% agree that it is difficult to find learning resources. As many as 35% of students have difficulty in analysing and solving problems, especially the heavy point and moment of inertia of the cross section. Respondents suggested that the E-module will make the formula points, references to example problems and practice problems are reproduced. In general, the results of this needs analysis can be used as a guide in designing teaching materials for Mechanics of Materials.